Morphological and DNA Barcoding Evidence Confirms the Presence of Semaprochilodus taeniurus (Prochilodontidae) in the Peruvian Amazon Basin - Ruiz-Tafur, M.; Chuctaya, J.; Castro-Ruiz, D.; Angulo, C.; Garcia-Davila, C.; Garcia-Ayala, J. R. [UNESP] (Pleiades Publishing, 2024)
Abstract: Semaprochilodus taeniurus (Valenciennes 1821) are known to inhabit the middle and lower regions of the Amazon basin. This study presents the first record of this species in the Peruvian Amazon, in the Lizardo stream, a tributary of the Putumayo River, Loreto region. The specimens were identified using meristic, morphological, and morphometric features as well as DNA barcodes based on the mitochondrial COI gene. This new species record contributes to enhancing our understanding of fish diversity in the Peruvian Amazon.
Keywords: biogeography; diversity; freshwater fishes; Loreto; new record